Potassium fertilization in the improved lines and landrace material of chile soledad (Capsicum annuum L.) - Ramírez-Seañez, Ana Rosa; Alfonso-García, José Mauricio; Hernández-Hernández, Hipólito; Palacios-Torres, Rogelio Enrique; Ramírez-Meraz, Moisés; Borroel-García, Victoria Jared (Ecosistemas y Recursos Agropecuarios, 2023)
Potassium is considered one of the most important fertilizers since it directly affects essential physiological functions of crops, the inadequate application of this element and the use of  landrace material often affect the quality and yields of various crops. The objective of this research was to evaluate the effect of two doses of potassium fertilization: Fertilization one: 260N-60P-440K 40Ca-30Mg and Fertilization two: 260N-60P-340K 40Ca-30Mg on morphology, fruit quality, and yield. in improved lines and landrace material from Chile Soledad under rainfed conditions. Six treatments were established T1: Fertilization 1 P15, T2: Fertilization 2 P15, T3: Fertilization 1 P13 and T4: Fertilization 2 P13 and two controls: T5: Fertilization 1 Creole material, and F6: Fertilization 2 Creole material. The experimental design was completely randomized blocks, with four repetitions. The improved line P15 (CHISER 522) with fertilization two, obtained the best yield results per plant and total with 489.43 g and 14.77 t ha-1, respectively, In addition, in morphology: plant height 77.73 cm, stem diameter 14.78 mm, crown width 64.43 cm, except for the number of ramifications. For fruit quality in the classification of large size fruits, the plants with the Fert 1 P15 treatment obtained the best results in terms of weight, length and diameter with 8.60 g, 9.83 cm and 13.06 mm respectively. The improved line P15 in combination with low potassium dose fertilization showed significant effects on the morphology and yield of this crop.